Active and transformative learning in STEAM disciplines : from curriculum design to social impact - Lytras, Miltiadis D. (Emerald Publishing Limited, 2023)
Active and Transformative Learning in STEAM Disciplines is a unique reference volume for the new student-centric and objectives-oriented learning environment where individual and team learning paths enhance problem solving capabilities. These practices may range from simple teaching methods such as class discussion and role playing, to peer teaching and flipped learning. Focusing on STEAM education (science, technology, engineering, arts and mathematics), scholars from the three disciplines of education, business, and Information Technology highlight the importance of the class as a place for collaborative knowledge sharing, involving active engagement of both students and instructors, and explore the connection between innovation and sustainability at the curriculum and research levels. Chapter authors discuss the timely issues of digital transformation in higher education, the required active learning strategies, the novel methodological approaches to instructional design and the new student-centric paradigm for active and collaborative exploration of learning content. Filling a significant gap in the body of knowledge related to the emerging agenda of active and transformative learning strategies for STEAM disciplines, this volume is a helpful tool to faculty, higher education administrators, policymakers, curriculum designers and school leaders aiming to develop value-based strategies for promoting quality education with an emphasis on active and transformative learning.
Includes index.
Keywords: Education, Higher.; Active learning.; Transformative learning.; Education -- Teaching / Methods & Strategies.; Teaching skills & techniques.; elektronické knihy; electronic books